Cyclic Peptide [R4W4] in Improving the Ability of First-Line Antibiotics to Inhibit Mycobacterium tuberculosis Inside in vitro Human Granulomas - Hernandez, Joshua; Ashley, David; Cao, Ruoqiong; Abrahem, Rachel; Nguyen, Timothy; To, Kimberly; Yegiazaryan, Aram; Akinwale David, Ajayi; Kumar Tiwari, Rakesh; Venketaraman, Vishwanath (Frontiers in Immunology, 2020)
Abstract: Tuberculosis (TB) is currently one of the leading causes of global mortality. Medical non-compliance due to the length of the treatment and antibiotic side effects has led to the emergence of multi-drug resistant strains (MDR) of Mycobacterium tuberculosis (M. tb) that are difficult to treat. A current therapeutic strategy attempting to circumvent this issue aims to enhance drug delivery to reduce the duration of antibiotic regimen, or dosage of first-line antibiotics. One such agent that may help is cyclic peptide [R4W4], as it has been shown to have antibacterial properties (in combination with tetracycline) against methicillin-resistant Staphylococcus aureus (MRSA) in the past. The objective of this study is to use cyclic peptide [R4W4] in combination with current first line antibiotics (isoniazid and pyrazinamide) to study the effects of inhibition of M. tb inside in vitro human granulomas. Results from our studies indicate that R4W4 is efficacious in controlling M. tb infection in the granulomas and has additive effects in the presence of first-line antibiotics.